2023
DOI: 10.1515/med-2023-0716
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of immunogenic cell death-related subtypes for predicting prognosis and immunotherapy outcomes in glioblastoma multiforme

Abstract: Immunogenic cell death (ICD), a unique form of cancer cell death, has therapeutic potential in anti-tumour immunotherapy. The aim of this study is to explore the predictive potential of ICD in the prognosis and immunotherapy outcomes of glioblastoma multiforme (GBM). RNA sequencing data and clinical information were downloaded from three databases. Unsupervised consistency clustering analysis was used to identify ICD-related clusters and gene clusters. Additionally, the ICD scores were determined using princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
3
1
Order By: Relevance
“…Our study, compared to this research, conducted a more in‐depth analysis of patient survival, immune microenvironment, and clinical features based on the subtypes of the ICD score. In previous studies, the high‐ICD subtype, derived from ICD genes, has been considered a protective factor for prognosis in HNSCC, lung adenocarcinoma, and ESCA, but a risk factor in pancreatic cancer and glioblastoma multiforme 10–13,27 . However, our results showed that a high ICD score was a protective factor for ACC, SKCM, and SARC, but a risk factor for UVM and LAML.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Our study, compared to this research, conducted a more in‐depth analysis of patient survival, immune microenvironment, and clinical features based on the subtypes of the ICD score. In previous studies, the high‐ICD subtype, derived from ICD genes, has been considered a protective factor for prognosis in HNSCC, lung adenocarcinoma, and ESCA, but a risk factor in pancreatic cancer and glioblastoma multiforme 10–13,27 . However, our results showed that a high ICD score was a protective factor for ACC, SKCM, and SARC, but a risk factor for UVM and LAML.…”
Section: Discussioncontrasting
confidence: 72%
“…In previous studies, the high-ICD subtype, derived from ICD genes, has been considered a protective factor for prognosis in HNSCC, lung adenocarcinoma, and ESCA, but a risk factor in pancreatic cancer and glioblastoma multiforme. [10][11][12][13]27 However, our results showed that a high ICD score was a protective factor for ACC, SKCM, and SARC, but a risk factor for UVM and LAML. The reason for differences in analysis results may be the method of consensus clustering used to distinguish ICD-associated subtypes.…”
Section: The Immunogenic Features Between the High Icd Cohorts And Lo...mentioning
confidence: 98%
See 2 more Smart Citations